2020
DOI: 10.17478/jegys.768134
|View full text |Cite
|
Sign up to set email alerts
|

The effect of PjBL plus 4Cs learning model on critical thinking skills

Abstract: The PjBL Plus 4Cs is an alternative learning model for geography. The PjBL Plus 4Cs can teach, train, and improve critical thinking skills. The research aimed to find out the effect of the PjBL plus 4C learning model on critical thinking skills. The research used a quasi-experimental design with a pretest-posttest nonequivalent control group approach. Students of Class XI IPS-1 and XI IPS-2 in Islamic Senior High School of Sabilillah Malang were the subjects of this research. Critical thinking skills were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…The results from quantitative data and qualitative data revealed that students' critical thinking skills increased significantly after the implementation of project-based writing instruction in terms of analyzing, reasoning, evaluating, decision-making, and problem-solving skills. These positive results concurred with previous studies (e.g., Beckett & Miller, 2006;Efendi et al, 2020;Fatmawati, 2018;Gujral & Adipattaranan, 2018;Zhang, 2018) reporting that project-based learning helped promote critical thinking skills of students. Interestingly, the results gained from various research instruments including the pre-and post-tests, the stimulated recall, the attitude questionnaire, and the semi-structured interview protocol yielded similar findings despite some variations.…”
Section: The Effects Of Project-based Writing Instruction On Improvem...supporting
confidence: 91%
See 1 more Smart Citation
“…The results from quantitative data and qualitative data revealed that students' critical thinking skills increased significantly after the implementation of project-based writing instruction in terms of analyzing, reasoning, evaluating, decision-making, and problem-solving skills. These positive results concurred with previous studies (e.g., Beckett & Miller, 2006;Efendi et al, 2020;Fatmawati, 2018;Gujral & Adipattaranan, 2018;Zhang, 2018) reporting that project-based learning helped promote critical thinking skills of students. Interestingly, the results gained from various research instruments including the pre-and post-tests, the stimulated recall, the attitude questionnaire, and the semi-structured interview protocol yielded similar findings despite some variations.…”
Section: The Effects Of Project-based Writing Instruction On Improvem...supporting
confidence: 91%
“…Based on an extensive review of literature on the effectiveness of project-based instruction (Al Sharadgah, 2014;Busciglio, 2016;Dudeney & Hockly, 2007;Efendi et al, 2020;Fatmawati, 2018;Ferris & Hedgcock, 2014;Gujral & Adipattaranan, 2018;Indah, 2017;Newprasit & Seepho, 2015;Stoller, 2012;Zhang, 2018), it could be assumed that project-based writing instruction could enable students to improve their writing ability together with critical thinking skills. Therefore, the hypotheses of this study were formulated as follows:…”
Section: Research Hypothesesmentioning
confidence: 99%
“…The PjBL model in its implementation does not only train to work in groups but also trains the independence of each student [13][14]. Teaching materials based on the PjBL model can also improve students' understanding of concepts, scientific process skills, and scientific attitudes [15].…”
Section: Figure 8 Validation Results For the Aspects Of Portfolio Ass...mentioning
confidence: 99%
“…Selain itu, dalam pembelajaran, mereka didorong untuk berpikir kritis dalam menanggapi isu-isu di sekitarnya (Thenga, Goldschagg, Fergusin, dan Mandikonza, 2020). Berpikir kritis merupakan salah satu jenis berpikir High Order Thinking Skills (HOTS) pada tingkat kognitif C-4 sampai C-5 dalam taksonomi Bloom, termasuk analisis, sintesis, dan evaluasi (Efendi, Sumarmi, & Utomo, 2020).…”
Section: Pendahuluanunclassified